2021
DOI: 10.1007/s10551-021-04806-3
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Gender on Investors’ Judgments and Decision-Making

Abstract: We examine whether an unsophisticated investor's own gender interacts with gender of a sell-side equity analyst to affect the investor's judgment. Prior research shows two potential sources of gender-based discrimination that affect female investors. First, female investors' advisors offer less risky hence lower return portfolios to female investors than to male investors with similar risk preferences as female investors are perceived as more risk adverse. Second, female equity analysts are subject to greater … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 144 publications
(147 reference statements)
0
3
0
Order By: Relevance
“…While many studies on financial decision-making claim that people act rationally when making decisions, more recent research shows that emotions and personality traits also play a significant role in decision-making (Wynes, 2021; Dibb et al ., 2021; Griffith et al ., 2020). More specifically, gender stereotyping/gender differences have often been well-documented and imply that female counterparts are more risk averse than their male counterparts when making decisions and are less competent in statistical calculations and finance than men, which contributes to underrepresentation of female counterparts in financial decision-making (Bottazzi and Lusardi, 2021; Luo and Salterio, 2022). Several studies linking gender stereotyping with financial decision-making highlight that females perceive financial decision-making as a traumatic and time-consuming process (Daruvala, 2007; Luo and Salterio, 2022; Kaur and Vohra, 2012; Carr and Steele, 2010; Bottazzi and Lusardi, 2021; Bacha and Azouzi, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While many studies on financial decision-making claim that people act rationally when making decisions, more recent research shows that emotions and personality traits also play a significant role in decision-making (Wynes, 2021; Dibb et al ., 2021; Griffith et al ., 2020). More specifically, gender stereotyping/gender differences have often been well-documented and imply that female counterparts are more risk averse than their male counterparts when making decisions and are less competent in statistical calculations and finance than men, which contributes to underrepresentation of female counterparts in financial decision-making (Bottazzi and Lusardi, 2021; Luo and Salterio, 2022). Several studies linking gender stereotyping with financial decision-making highlight that females perceive financial decision-making as a traumatic and time-consuming process (Daruvala, 2007; Luo and Salterio, 2022; Kaur and Vohra, 2012; Carr and Steele, 2010; Bottazzi and Lusardi, 2021; Bacha and Azouzi, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, gender stereotyping/gender differences have often been well-documented and imply that female counterparts are more risk averse than their male counterparts when making decisions and are less competent in statistical calculations and finance than men, which contributes to underrepresentation of female counterparts in financial decision-making (Bottazzi and Lusardi, 2021; Luo and Salterio, 2022). Several studies linking gender stereotyping with financial decision-making highlight that females perceive financial decision-making as a traumatic and time-consuming process (Daruvala, 2007; Luo and Salterio, 2022; Kaur and Vohra, 2012; Carr and Steele, 2010; Bottazzi and Lusardi, 2021; Bacha and Azouzi, 2019). In line with this, Goyal and Kumar (2021) conducted a bibliographic analysis of 175 studies and found that financial literacy among female consumers, financial inclusion and gender differences were some of the major themes that were investigated in the field of financial decision-making.…”
Section: Introductionmentioning
confidence: 99%
“…Since traditional financial methods are exclusively reliant on analyzing the historical trading data of the stock market (e.g., investors' stock age and cumulative number of stocks traded) [13][14][15], it is hard for researchers to isolate the independent contributions of investment experience and control the irrelevant variables such as gender, risk tolerance, emotion, age, financial literacy, etc. [16][17][18][19][20]. Numerous confounding variables will covariate with the variables of interest, obscuring the interested effects [21][22][23].…”
Section: Introduction 1two Contrasting Views On Whether Investment Be...mentioning
confidence: 99%